Numerical study on equilibrium stability of objects in fluid flow — A case study on constructal law. (November 2019) - Deng, Changyu; Qi, Xin; Liu, Yingwen
Abstract: Stability of objects in fluid flow is an interesting and significant subject in many fields. From thermodynamics point of view, the constructal law by Bejan et al. proposed that in some scenario, objects tend to be stable when the drag reaches maximum. To investigate the relation between drag and stable positions, we analyzed two simple cases by the finite element method: an elliptical cylinder and a rectangular cylinder immersed in 2D uniform laminar flow. The ellipse is stable when its major axis is perpendicular to the mainstream and the drag reaches maximum; yet the rectangle is stable when the length is perpendicular to the mainstream, with drag ranging from minimum to maximum depending on its aspect ratio. Our results show that there is no universal relation between drag and stability.